Uwagi w sprawie genezy i charakteru hajdamaczyzny na prawobrzeżnej Ukrainie - Srogosz, Tadeusz (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
There are differences between Polish, Ukrainian and Russian historiography as regards the genesis and nature of the haidamaks. The issue of genesis is less controversial. Rather, there is a consensus about 1717 as not so much a turning point as the date of first use of the term (possibly 1715). Polish historians do not associate the origins of haidamaks directly with social unrest, while Ukrainian and Russian historians claim that haidamaks had its roots in the events in Right-bank Ukraine at the beginning of the 18th century. Moreover, the haidamak tradition was to be a continuation of the Cossack tradition. Ukrainian and Russian historiography places the genesis and character of haidamaks strongly in the socio-religious context, as a result of the oppression of the Polish nobility and Jewish leaseholders, as well as of the religious conflict. In Polish historiography, the above conditions are either absent or the importance of social, religious and national conflicts is recognized. In Polish historiography, the robber nature of the haidamaks was pointed out. In turn, the so-called social robbery was emphasized in Ukrainian historiography, the haidamaks were participants in national movements with a social background.